Risk Analysis in a Portuguese Archive: What Has Changed in Five Years?. Issue 1 (March 2013) - Pinheiro, A. C.; Moura, L.; Sequeira, S.; Viegas, C.; Viegas, S.; Macedo, M. F.
The Cultural Property Risk Analysis Model was applied in 2006 to a Portuguese archive located in Lisbon. Its results highlighted the need for the institution to take care of risks related to fire, physical forces and relative humidity problems. Five years after this first analysis the results are revisited and a few changes are introduced due to recent events: fire and high humidity remain an important hazard but are now accompanied by a pressing contaminants problem. Improvements in storage systems were responsible for a large decrease in terms of calculated risk magnitude and proved to be very cost-effective.